Comparative evaluation of antimicrobial peptides: effect on formation, metabolic activity and viability of Klebsiella pneumoniae biofilms - Sophia Hanstein; Thomas Grochow; Marina Mötzing; Marina Mötzing; Simone A. Fietz; Ralf Hoffmann; Ralf Hoffmann; Christoph G. Baums; Sophie Kähl (Frontiers in Microbiology)
IntroductionKlebsiella pneumoniae (K. pneumoniae) is a major human nosocomial infectious agent and an important veterinary pathogen, frequently resistant to various antibiotics. It causes diseases such as pneumonia, urinary tract infections, surgical wound infections and septicemia. Biofilm formation of K. pneumoniae promotes persistent infection and contributes to resistance against antimicrobial agents. The objective of this study was to comparatively evaluate the effect of selected AMPs on the formation, metabolic activity and viability of Klebsiella pneumoniae biofilms of veterinary and human origin.MethodsBiofilm formation of three K. pneumoniae strains was quantified using the crystal violet assay and visualized by scanning electron microscopy (SEM). The inhibitory effects of eight different AMPs on the formation and metabolic activity of K. pneumoniae biofilms, as well as on planktonic growth, were examined using crystal violet, resazurin and broth microdilution assays, respectively. The effect on living and dead bacteria in mature biofilms was investigated using the fluorescent dyes SYTO™ 9 and propidium iodide. In addition, the distribution of rhodamine B-labeled peptide DJK-5 in mature biofilms of strain 17349 was visualized by confocal laser scanning microscopy (CLSM).ResultsBiofilm formation was confirmed for all three K. pneumoniae strains. Depending on the strain, we found that planktonic growth was affected by the AMPs DJK-5, DJK-6, Onc72, and Onc112. Biofilm formation of all three strains was inhibited by hbD3, LL-37, DJK-5, and DJK-6, with biofilm mass reduced to less than 40% of the untreated control. In addition to the inhibition of biofilm formation, a reduction in the metabolic activity of the biofilm-associated bacteria was also observed. These four AMPs also showed an effect on mature biofilms by reducing the number of both viable and dead bacteria in 22 h-old biofilms. Rhodamine B-labeled DJK-5 took 7 h to visibly accumulate in the planktonic bacteria. Multi-layered biofilm aggregations were mainly negative for rhodamine B-labeled DJK-5, even 44 h after AMP treatment, indicating that certain parts of mature K. pneumoniae biofilms are not accessible for this AMP.ConclusionIn conclusion, we found differences in the effect of AMPs on biofilms including both increases and decreases in biofilm mass and viability.